Examining Studio Ghibli's Animated Films: A Study of Students' Viewing Paths and Creative Projects. Issue 6 (30th January 2020) - Williams, Wendy R.
Abstract: Being literate in today's world involves more than reading and writing traditional works in print. Students need experiences with a range of multimodal narratives, including animation. Multimodal narratives offer many entry points for engagement, and design plays an important role as readers/viewers navigate their way through these works and make meaning. This qualitative study took place in the U.S. Southwest and involved 20 university students enrolled in a Studio Ghibli Films course. Analysis of coursework using grounded theory and open coding revealed that participants designed nine viewing paths to interpret the films, approaching animated works as narratives, multimodal compositions, cultural/historical artifacts, transformed source materials, products of a director, objects of value, conversations between texts, commentaries, and personal experiences. Participants also composed a wide variety of creative projects that drew on their out‐of‐school interests. Animated works, such as the films of Studio Ghibli, have great potential in education.